Transformation of Silicon Nanowire into Nanopyramid in Alkaline Solution and its Implication in Silicon‐Air Battery. (29th June 2016) - Sarwar, Saad; Kim, Minsun; Baek, Giljae; Oh, Ilwhan; Lee, Hochun
Abstract : Si–air battery (SAB) comprising of Si nanowire (SiNW) anode and alkaline solution and showing a working voltage of ca. 1.2V is investigated to elucidate the origin of superior discharge performance of the nanostructured Si anode to that of a planar Si anode. The SiNWs are found to transform into Si nanopyramids (SiNPs) upon immersion in the alkaline solution or when subjected to SAB discharge. In this regard, the improved performance of the SiNW anode is attributed to the formation of SiNPs with (111) facets that are intrinsically resistant to passivation. In addition, the nanostructured Si anode also shows a lower threshold temperature for the surface passivation than the planar Si anode, a merit that leads to a sustained discharge even at room temperature. Abstract :